Therapeutic Impact of Fun Learning on Depression Level Among Students at Selected School in Hospital - Kandasamy, Premma; Tahar, Mohd Mokhtar (Department of Special Education, 2020)
This study aims to look at the effectiveness of therapeutic use of amusement on Depression In School In The Hospital. This study aimed to identify levels of depression among SDH students through behavioral observation using the DSM-5 scale and to explain the therapeutic impact of the amusement-based approach on the depression of SDH students using the Child Depression Inventory. This study used a qualitative approach to collect data. Therefore, this study uses approaches such as observations and interviews. The study population was SDH students/patients at the University of Malaya Medical Centre. The sample consisted of 24 SDH students selected for purposive sampling. Two research instruments used in this study were DSM -5 and Child Depression Inventory. This study shows that the therapeutic effect of education has been successful in reducing the depression of School In hospital students. Overall, this study shows that the effect of therapeutic use on entertainment is an appropriate and effective form of intervention.